An Investigation on the Synthesis of Molybdenum Oxide and Its Silica Nanoparticle Composites for Dye Degradation - Olfa Kamoun; Abdelaziz Gassoumi; Salah Kouass; Badriyah Alhalaili; Ruxandra Vidu; Najoua Turki-Kamoun (Nanomaterials, 2020)
The molybdenum oxide (MoO3) and MoO3@SiO2 nanoparticles were successfully prepared using the chemical bath deposition (CBD) method. The photocatalytic activities of molybdenum oxide (MoO3), SiO2, and MoO3@SiO2 nanoparticles composite have shown a synergistic photocatalytic effect of SiO2 combined with MoO3. The first-order degradation rate constants for MoO3, SiO2, and MoO3@SiO2 nanocomposite were 10.3 × 10−3 min−1, 15.1 × 10−3 min−1, and 16.3 × 10−3 min−1, respectively. The MoO3@SiO2 composite showed degradation efficiencies in the methylene blue solution close to 100% after 60 min of UV irradiation. The X-ray diffraction (XRD) showed that the MoO3 powder has a hexagonal crystal structure and the silica is the tridymite type of SiO2. The crystallite size was about 94 nm, 32 nm, and 125 nm for MoO3, silica, and MoO3@SiO2, respectively, as calculated by the Scherrer equation. The scanning electron microscopy (SEM) images revealed that the MoO3 powder consisted of a uniform hexagonal structure; the silica showed a rod-like micro-flake morphology and the MoO3@SiO2 composite had the appearance of coral-like structures.